On the Validation of Cost Push: A Comment. - Wren-Lewis, S (Elsevier, 1983)
A recent article in this journal examined the effects of ‘cost-push’ disturbances in a model in which government expenditure was fixed in nominal rather than real terms. It was suggested that, under certain circumstances, these nominal government expenditure targets could destabilise the model. In this note we show that, on the contrary, this particular model is always stable, whether or not government expenditure is fixed in nominal or real terms.